Best Answer

Ln 4 + 3Ln x = 5Ln 2

Ln 4 + Ln x3= Ln 25 = Ln 32

Ln x3= Ln 32 - Ln 4 = Ln (32/4) = Ln 8= Ln 2

Q: How would you solve ln 4 plus 3 ln x equals 5 ln 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3lnx - ln2=4 lnx^3 - ln2=4 ln(x^3/2)=4 (x^3)/2=e^4 x^3=2e^4 x=[2e^4]^(1/3)

Wiki answer limits your ability to insert operators in questions, so please write out the word "equals" or "plus" as it is necessary.

ln is the inverse of e. So the e and the ln cancel each other out and you are left with 2. eln2 = 2

if x8 = 20 then x = - eighth root of 20 or x = eighth root of 20 eighth root of 20 = 1.4542154.... Maybe you mean 8x = 20 If so Ln (8x) = Ln (20) => x Ln(8)= Ln(20) => x = Ln(20)/Ln(8) = 1.4406426...

Yes, the function ln(x) where ln is the logarithm to base e.Yes, the function ln(x) where ln is the logarithm to base e.Yes, the function ln(x) where ln is the logarithm to base e.Yes, the function ln(x) where ln is the logarithm to base e.

Related questions

5 + (-4) = 1 x = -4

-3 + ln(x) = 5 ln(x) = 8 eln(x) = e8 x = e8 x =~ 2981

2 ln(9) + 2 ln(5) = 2 ln(x) - 3ln(81) + ln(25) = ln(x2) - 37.61332 = ln(x2) - 3ln(x2) = 10.61332ln(x) = 5.30666x = e5.30666 = 201.676 (rounded)

3 ln(x) = ln(3x)ln(x3) = ln(3x)x3 = 3xx2 = 3x = sqrt(3)x = 1.732 (rounded)

8958=e^(5x) ln both sides -> ln(8958)=5x Therefore x=1.82

Unfortunately, limitations of the browser used by WA means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc.

e3x+5 x ex =7 e3x+5+x=7 4x+5=ln(7) x=(ln(7)-5)/4

There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).

In the equation ln(x) = 5, the solution is x = (about) 148.4. To solve, simply raise e to the power of both sides and reduce... ln(x) = 5 eln(x) = e5 x = 148.4

e-x = 6Take the natural log of both sides:ln(e-x) = ln(6)-x = ln(6)x = -ln(6)So x = -ln(6), which is about -1.792.

If: u = 1+lnx Then: x = (u-1)/(ln)

ln(x+14)-lnx=3ln2 ln[(x+14)/x]=ln8 (x+14)/x=8 x+14=8x 14=7x 2=x x=2 Check this answer by plugging x=2 back into the original equation: ln(2+14)-ln(2)=3ln2 ln(16)-ln(2)=3ln2 ln(16/2)=3ln2 ln8=3ln2 3ln2=3ln2 There you go!